The Effect of Using The SFAE Learning Model of IPS Subject on Increasing School Elementary Students Learning Outcomes - Novitasari M; Sudarmin Sudarmin; Sri Wardani; Deni Setiawan; Edi Waluyo (International Journal of Active Learning, 2023)
The effect of using the sfae model to increase student learning outcomes in social studies subjects apply the modelÂ student facilitator and explaining learning. This type of research is classroom action research using a qualitative approach. This research carried out in 2 cycles. Each cycle includes the stages of planning, implementing, observation, and reflection. Data analysis techniques were carried out by reduction, reflection and draw a conclusion. Based on the results of data analysis, obtained data that shows an increase in student learning outcomes in each cycle. based on data obtained during the implementation of cycle I and cycle II that the results were obtained research in cycle I was in the sufficient category, and there was an increase in cycle II which is in the good category and achieves the indicators that have been set. So it can be concluded that classroom action research with apply the student facilitator and explaining learning model for improve student learning outcomes in social studies subjects in class V SDN has succeeded with the percentage of the average value of students in the good category and was appropriate with predetermined indicators of success.